KOMPARASI KEUNTUNGAN USAHA HATCHERY IKAN KERAPU HIBRIDA CANTIK DAN HIBRIDA CANTANG DI KECAMATAN GEROKGAK KABUPATEN BULELENG - Ni Nyoman Atik Dwi Putri Hartatik; Nyoman Yudiarini; Luh Putu Kirana Pratiwi (AGRIFARM (Jurnal Agribisnis dan Sosial Ekonomi Pertanian), 2023)
Compared to Cantik hybrid grouper seeds. However, the resistance to pathogen attack on the Cantang hybrid seeds was lower than that of the Cantik hybrid. Therefore, it is necessary to study the comparative profit of Cantang hybrid and Cantik hybrid grouper hatcheries. The aims of this study were to analyze the survival rate of the Cantik hybrid grouper and the Cantang hybrid grouper in Gerokgak District, and to analyze and test the comparison of the two hybrid grouper hatcheries. The method used was a survey of each of 12 sampels of hybrid hatcheries of Cantang and Cantik and analyzed the profit comparison of the two types of hatcheries using the two free sample test. The results showed that the average seed production of the Cantang hybrid grouper was 64,908 pieces with a survival rate of 12.89% from the number of eggs laid. The average seed production of Cantik hybrid grouper was 60,620 pieces with a survival rate of 12.38%. The profit of the Cantang hybrid grouper hatchery per production cycle is Rp. 54,813,226.00, while the profit of the Cantik hybrid grouper hatchery is Rp. 60,036,083.00. The difference between the profit of the grouper hatchery business of Cantik hybrid and Cantang hybrid is Rp. 5,222,857.00. However, this difference in profit is only significant at the test error rate of 0.20. From the results of this study, it is suggested to the hatchery business community to carry out joint management training in improving and pleasing hatchery workers. If grouper eggs for both types of hybrids are available, backyard farmers are advised to prioritize hatchery of Cantik hybrid groupers